Pelatihan Pengukuran Teknik Bagi Siswa SMA Islam Assa’adah Puri Serpong Tangerang Selatan - Budi Kaliwanto; Bambang Herlambang (Universitas 45 Surabaya, 2023)
Measurement is the process of comparing parameters on a being measured object against standardized one. It is an effort to obtain descriptive-quantitative information about the physical and chemical variables of a substance or object being measured, such as a length of 1 meter or a mass of 1 kilogram, and so forth. In everyday life, many objects require measurement for specific purposes in the workplace, at schools or campuses. Based on observations carried out at Assa’adah Islamic High School in Puri Serpong, South Tangerang, there are constraints related to measurement subjects such as lack of teaching competence, laboratories and practical equipment. Therefore, technical measurement training is needed for students at Assa’adah Islamic High School in Puri Serpong, South Tangerang, to enhance their knowledge and develop good skills in measuring technical equipment. The process of learning technical measurement at the high school should be supported by various factors, including student motivation, learning media, learning facilities, teacher motivation, and the teaching methods used by teachers. The result of the after training is that the knowledge and skills of the students related to technical measurement, increasing than before.